ANALISIS EKUITAS MEREK KARTU SELULER MENTARI (Suatu Survey Pada Pengguna Kartu Seluler Merek Mentari Di Regional Jawa Barat) - Rahma Wahdiniwaty (JURISMA : Jurnal Riset Bisnis & Manajemen, 2012)
ABSTRACTThe purpose of this research is to know respondent assessment on brand equity cellular card MentariThe research uses descriptive survey and explanatory survey method. The population research are cellular card user of Mentari brand in West Java Region. The sampling technique used is cluster judgment sampling with size of each stratum use proportional size with population stratum. The collection of data is conducted by observation technique, interview and questionnaire which first organize try-out to 30 respondents to saw its validity and reliability. Subsequently, if try-out to them was valid and reliable, then continued by disseminated questionnaire with sample of 425 respondents who use Mentari‟s cellular card which is distributed around the five cities/regencies that are Bandung, Tasikmalaya, Purwakarta, Cirebon, and Sukabumi. The qualitative analysis uses the category determination in the term of percentage for each sub-variable.The results of research indicate that Mentari equity is assessed high.Keywords :brand equity